Alienation among College students of Jammu and Kashmir in relation to their Emotional Maturity and Home Environment (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The present problem was taken up to explore the levels of alienation among college students of Jammu and Kashmir in relation to their emotional maturity and home environment. Study was conducted on a sample of 200 students of Jammu and Kashmir and results revealed that there is negative relationship in alienation and emotional maturity among college students of Jammu and Kashmir. There is no significant relationship in alienation and home environment college students of Jammu and Kashmir college students of Jammu and Kashmir which means that alienation is not due to home environment. There is no significant positive relationship between emotional maturity and home environment among college students of Jammu and Kashmir.